Elephant Flow Classification on the First Packet With Neural Networks - Bartosz Kadziolka; Piotr Jurkiewicz; Robert Wojcik; Jerzy Domzal (IEEE Access, 2024)
Quick and accurate identification of the largest flows in the network would allow for the management of most traffic using dedicated, flow-specific routes and policies, thereby significantly reducing the overall number of entries in switch flow tables. Our analysis focuses on utilizing neural networks to classify elephant flows based on the first packet using 5-tuple packet header fields. The findings indicate that with simple neural networks comprising solely linear layers, it is possible to accurately detect elephant flows at their inception, thereby reducing the number of flow table entries – by up to a factor of 15 – while still effectively covering 80% of the network traffic with individual flow entries.